Bone resorption as a marker for delayed esophageal perforation post anterior cervical spine surgery: a retrospective analysis and call for increased vigilance - Hua Luo; Zhangfu Wang; Shuang Mi; Guangyong Yang; Wenjun Pan; Xingbing Feng; Zhenghua Hong (Frontiers in Medicine, 2024)
PurposeDelayed esophageal perforation following anterior cervical spine surgery (ACSS) is a rare but serious complication. This study is to investigate the clinical characteristics, diagnostic approaches, and treatment outcomes of delayed esophageal perforation following ACSS, with a focus on the role of bone resorption around internal fixations as a potential diagnostic indicator.MethodsWe retrospectively analyzed patients diagnosed with delayed esophageal perforation after ACSS from January 2010 to December 2023 and described their clinical characteristics, diagnostic approaches, and treatment outcomes. Through the analysis of the differences in the radiomics of patients, we identified the possible clinical signs of esophageal perforation and shared our experience in treating esophageal perforation.ResultsA total of five patients met our criteria. All five patients exhibited bone resorption around their internal fixations on radiography. Although bone resorption typically suggests local infection, none of the patients showed clear signs of neck skin infection, leading us to suspect esophageal perforation as the underlying cause. Further diagnostic procedures including CT, MRI, esophagography, and endoscopy were crucial for confirming the diagnosis of delayed esophageal perforation and assessing its severity. All patients underwent surgical intervention involving implant removal and esophageal repair using a sternocleidomastoid muscle flap transfer. All patients recovered and were discharged after treatment, with no recurrence of symptoms during follow-up.ConclusionDelayed esophageal perforation should be considered in patients with neck pain or nonspecific symptoms after ACSS, especially with bone resorption around internal fixations. Clinicians should maintain high vigilance and use multimodal imaging and endoscopy for timely diagnosis. Our study indicates a significant link between bone resorption and delayed esophageal perforation despite the limited number of cases. Highlighting this association aims to raise awareness and encourage further research. Larger studies are needed to validate our findings, improve clinical guidelines, and ultimately enhance patient outcomes in orthopedics.